Enhancing the anisole hydrodeoxygenation activity over Ni/Nb2O5−x by tuning the oxophilicity of the support. Issue 4 (16th January 2023) - Ali, Hadi; Vandevyvere, Tom; Lauwaert, Jeroen; Kansal, Sushil Kumar; Sabbe, Maarten K.; Saravanamurugan, Shunmugavel; Thybaut, Joris W.
Abstract : Ni/Nb2 O5 -H, prepared via the hydrolysis method, possesses a higher number of oxygen vacancies and metal-support interface than Ni on commercial Nb2 O5 (Ni/Nb2 O5 -C), resulting in enhanced activity and selectivity towards deoxygenated products. Abstract : The present work focuses on designing a robust non-noble metal-based niobia-supported catalyst with a high number of oxygen vacancies for an efficient HDO activity of anisole. Various synthesis procedures, such as hydrothermal (Nb2 O5 -HT), precipitation (Nb2 O5 -P) and hydrolysis (Nb2 O5 -H), are adopted for the preparation of the Nb2 O5 support, followed by 3 wt% Ni impregnation. As a benchmark, Ni has also been impregnated on commercial Nb2 O5 (Nb2 O5 -C). The catalysts display a large discrepancy in surface areas, the crystallite size of Nb2 O5 and NiO x, strong metal–support interaction (SMSI), active interfacial Ni–NbO x species and oxygen vacancies. In particular, Ni impregnated on Nb2 O5 -H (Ni/Nb2 O5 -H) possesses the highest amount of oxygen vacancies (202 μmol g −1 ) (O2 -temperature programmed desorption), which is 1.1 and 3.5 fold higher than that for Ni/Nb2 O5 -HT and Ni/Nb2 O5 -P, respectively, indicating the importance of the synthesis procedure of the support. Interestingly Ni/Nb2 O5 -H has 200-fold higher oxygen vacancies than Ni/Nb2 O5 -C. Likewise, Ni/Nb2 O5 -H possesses a high Ni 3+ /Ni 2+ and Nb 4+ /Nb 5+ ratio, based on X-ray photoelectron spectroscopy, suggesting high dispersion of small NiO x particles on the NbO x surface, facilitating the redistribution of the electrons at the interface of NiO and Nb2 O5 due to SMSI. This leads to the formation of active interfacial Ni–NbO x species and oxygen vacancies (confirmed by H2 -TPD and XPS), contributing to the activation of hydrogen and anisole adsorption and thereby improving HDO activity substantially. At similar conversions of anisole, Ni/Nb2 O5 -H exhibits the highest rate of HDO of 0.63 mmol min −1 g −1, which is 1.4 to 3.2 fold higher than those of the other catalysts, including Nb2 O5 -C. Under optimised reaction conditions, Ni/Nb2 O5 -H shows a remarkable activity towards HDO of anisole with an excellent selectivity to cyclohexane (96.5%) at the near-quantitative conversion of anisole (>98%) at 240 °C, 20 bar H2, 2 h. Ni/Nb2 O5 -H also displays good to excellent activity towards various lignin-based model compounds, affording 50–96% cyclohexane yield.